2020
DOI: 10.1371/journal.pone.0244688
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil supplements, oxidative status, and compliance behaviour: Regulatory challenges and opportunities

Abstract: Background Fish oil supplements that are rich in omega-3 long-chain polyunsaturated fatty acids (n-3 PUFAs). PUFAs are among the most widely-used dietary supplements globally, and millions of people consume them regularly. There have always been public concerns that these products should be guaranteed to be safe and of good quality, especially as these types of fish oil supplements are extremely susceptible to oxidative degradation. Objectives The aim of the current study is to investigate and examine the ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…These higher levels could be attributed to the fact we used store-bought walnuts with an unknown harvest date while in both previous studies, walnuts were freshly harvested. The mean PV of the fish oil estimated in this study, 4.39 meq/kg, is similar to that purchased in Australia (range 2.77-4.63 meq/kg) [25] and the study by Zyoud and colleagues [26], who reported a combined mean PV of 6.4 meq/kg for fish oil capsules purchased in the USA, Canada, India, and the EU. The fact that our study demonstrated that the PV stayed the same after storage for three months and was within the maximum reference limit (5 meq/kg fat) set by the Global Organization of EPA and DHA (GOED) suggests that omega rich fish oil capsules are oxidatively stable in storage.…”
Section: Discussionsupporting
confidence: 85%
“…These higher levels could be attributed to the fact we used store-bought walnuts with an unknown harvest date while in both previous studies, walnuts were freshly harvested. The mean PV of the fish oil estimated in this study, 4.39 meq/kg, is similar to that purchased in Australia (range 2.77-4.63 meq/kg) [25] and the study by Zyoud and colleagues [26], who reported a combined mean PV of 6.4 meq/kg for fish oil capsules purchased in the USA, Canada, India, and the EU. The fact that our study demonstrated that the PV stayed the same after storage for three months and was within the maximum reference limit (5 meq/kg fat) set by the Global Organization of EPA and DHA (GOED) suggests that omega rich fish oil capsules are oxidatively stable in storage.…”
Section: Discussionsupporting
confidence: 85%
“…The UAE and other national drug regulatory authorities require dietary or herbal supplements to be manufactured in plants that demonstrate that their production follows strict good manufacturing practice guidelines and that any new products are tested in government or approved laboratories. Nevertheless, cases have been reported of dietary supplements being approved and put on the market despite being contaminated with microorganisms (Consumer Products Safety Section [ 11 , 12 , 13 ]). While the ministry responsible for the regulation of these products has warned citizens about the associated risks of consuming the sexual enhancement products, such as serious side effects, they remain widely available, especially through illegal online suppliers.…”
Section: Introductionmentioning
confidence: 99%
“…In the UAE regulatory regime, the manufacturers of dietary supplements must supply evidence that their product manufacturing environment guarantees their products are safe and pure; any new product must be tested in municipal laboratories. Nevertheless, despite these safeguards, there have been cases where microorganism-contaminated dietary supplements have gained approval and been offered for sale [25][26][27].…”
Section: Introductionmentioning
confidence: 99%